Green low-carbon concrete and preparation method thereof

CN119638279BActive Publication Date: 2026-10-23CHINA STATE CONSTR READY MIXED CONCRETE CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411444096.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2026-10-23
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

[0004]本发明的主要目的在于针对城市固废消纳、商品混凝土中原材料碳排放量高、成本高等问题,提供一种新型绿色低碳混凝土,采用基于全固废低碳原材料稻壳灰、收尘石粉、钢渣粉的胶凝材料体系,可实现混凝土的低碳生产,并可兼顾良好的工作性能和力学性能;且涉及的制备方法较简单,操作方便,成本较低,适合推广应用

Benefits of technology

[0025]1)本发明采用基于稻壳灰、收尘石粉和钢渣粉的全固废胶凝体系,首先采用高能球磨机进行研磨,增加其比表面积和反应活性,促使硅酸根离子(SiO32-)与钙离子(Ca2+)的结合,形成硅酸钙化合物;同时促进三种固废之间产生化学变化,使所得混合物具有良好的胶凝性;然后将研磨后的混合料进行加热稳定处理,热稳定处理可增加材料化学结构稳定性并促进胶凝性质稳定。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses green low-carbon concrete, and each raw material and weight percentage thereof comprise: rice husk ash 100-140 parts, dust collecting stone powder 140-180 parts, steel slag powder 100-140 parts, sand 780-880 parts, stone 950-1100 parts, activator 4-10 parts, water reducing agent 6-10 parts, and water 170-180 parts; wherein, the rice husk ash, the dust collecting stone powder and the steel slag powder are first ground and heated and stabilized to form low-carbon composite cementitious material.The application adopts a full solid waste raw material system based on the rice husk ash, the dust collecting stone powder and the steel slag powder, sequentially carries out high-energy grinding and heating and stabilization treatment, forms the low-carbon composite cementitious material with high activity, and simultaneously combines the activator, so that the adverse influence of the alkali-silicate reaction brought by the rice husk ash on the system can be effectively inhibited; the obtained concrete can consider good working performance and mechanical performance and the like, and the preparation method is relatively simple, convenient to operate, low in cost and suitable for popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of building materials technology, specifically relating to a green low-carbon concrete and its preparation method. Background Technology

[0002] With the rapid development of global industrialization, the generation of various industrial solid wastes has increased dramatically. How to effectively treat and utilize these solid wastes has become an urgent environmental problem. Rice husk ash, dust collector stone powder, and steel slag powder are three typical industrial solid wastes. Their large-scale accumulation not only occupies valuable land resources but also may cause serious pollution to the surrounding environment. Therefore, developing a technology that can transform these solid wastes into high-value-added products is particularly important.

[0003] Currently, the utilization rate of the above three solid waste materials as cementitious materials is low. The main reasons include low activity, poor cementitious properties, and limited filling benefits. For example, the allowable filling amount of rice husk ash is small, generally less than 25% of the mass of the filled material, and it can usually only play a supplementary role in reducing costs. In addition, once the filling amount is large, the reinforcing effect will be significantly reduced. The activity of dust-collecting stone powder is significantly lower than that of cement clinker, so the amount of cement clinker participating in the initial hydration will be reduced, leading to problems such as reduced concrete strength. Summary of the Invention

[0004] The main objective of this invention is to address the problems of high carbon emissions and high costs associated with urban solid waste disposal and raw materials in commercial concrete by providing a novel green and low-carbon concrete. This invention employs a cementitious material system based on low-carbon raw materials from all solid waste, such as rice husk ash, dust-collecting stone powder, and steel slag powder. This system enables low-carbon concrete production while maintaining good workability and mechanical properties. Furthermore, the preparation method involved is relatively simple, easy to operate, and low in cost, making it suitable for widespread application.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0006] A green low-carbon concrete comprises the following raw materials and their respective weight proportions: 100-140 parts rice husk ash, 140-180 parts dust-collecting stone powder, 100-140 parts steel slag powder, 780-880 parts sand, 950-1100 parts stone, 4-10 parts activator, 6-10 parts water-reducing agent, and 170-180 parts water; wherein, the rice husk ash, dust-collecting stone powder, and steel slag powder are first ground and heated to stabilize them to form a low-carbon composite cementitious material.

[0007] In the above scheme, the SiO2 content in the rice husk ash is >85%, the activity index is >90%, and the median particle size D50 is <6um.

[0008] In the above scheme, the fineness of the dust-collecting stone powder on a 45µm sieve is 9-13%, the 28-day activity index is greater than 70%, and the water requirement ratio is 95-105%.

[0009] In the above scheme, the median particle size D50 of the steel slag powder is less than 5 μm, the 28-day activity index is greater than 70%, and the specific surface area is greater than 450 m². 2 / kg.

[0010] In the above scheme, the grinding step uses a rotation speed > 500 r / min, a grinding time of 3 to 5 h, and a ball-to-material ratio of 10 to 15:1.

[0011] Further, after grinding, the resulting powder is heated and stabilized, then cooled to obtain a low-carbon composite cementitious material.

[0012] In the above scheme, the heating stabilization treatment is carried out at a temperature of 110-150℃ for 2-6 hours.

[0013] In the above scheme, the activator is a sulfate activator, specifically gypsum or sodium sulfate, etc.

[0014] In the above scheme, the fineness modulus of the sand is 2.5 to 2.8, and it is medium sand in zone two; the stone has a continuous gradation of 5 to 25 mm, and the content of needle-like and flaky particles is less than 6%.

[0015] In the above scheme, the water reduction rate of the water-reducing agent is 15-25%.

[0016] The above-mentioned method for preparing green and low-carbon concrete includes the following steps:

[0017] 1) Weighing of raw materials: each raw material and its weight percentage include: 80-120 parts rice husk ash, 120-160 parts dust collection stone powder, 80-120 parts steel slag powder, 780-880 parts sand, 950-1100 parts stone, 4-10 parts activator, 6-10 parts water reducing agent, and 170-180 parts water.

[0018] 2) Mix the weighed rice husk ash, steel slag powder, and dust collection stone powder, then grind them, then heat and stabilize them, and cool them to obtain a low-carbon composite cementitious material.

[0019] 3) First, mix some water with the water-reducing agent evenly to obtain a water-reducing agent solution. Add the water-reducing agent solution into the mixer, add the low-carbon composite cementitious material, and then add the activator under stirring conditions.

[0020] 4) Continue to add sand and stone in sequence under mixing conditions, mix and process, and add the remaining water during this process, which is low-carbon early-strength concrete.

[0021] In the above scheme, in step 3), 40-70% of the amount of water is added first.

[0022] In the above scheme, the stirring conditions in step 3) are continuous stirring for 2 to 3 minutes, and the stirring time in step 4) is continuous stirring for 3 to 5 minutes.

[0023] The green low-carbon concrete prepared according to the above scheme has an initial slump of 160-200mm, an initial spread of 220-250mm, a 3-day compressive strength greater than 17MPa, and a 28-day compressive strength greater than 42.5MPa.

[0024] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0025] 1) This invention employs a solid waste cementing system based on rice husk ash, dust-collecting stone powder, and steel slag powder. First, a high-energy ball mill is used for grinding to increase its specific surface area and reactivity, promoting the formation of silicate ions (SiO3). 2- ) and calcium ions (Ca 2+ The combination of these substances forms calcium silicate compounds; at the same time, it promotes chemical changes among the three solid wastes, giving the resulting mixture good gelling properties; then the ground mixture is subjected to heat stabilization treatment, which can increase the chemical structure stability of the material and promote the stability of gelling properties.

[0026] 2) When the cementing system (low-carbon composite cementing material) described in this invention is dissolved in water, the calcium hydroxide produced by the hydrolysis of dust collection stone powder can effectively activate the active components such as silicon dioxide and aluminum oxide in rice husk ash and steel slag powder, which can promote the further formation of hydrated calcium silicate products with cementing properties and provide the main strength of the cementing system.

[0027] 3) Steel slag powder and sulfate activators can work together to effectively suppress the adverse effects of alkali-silicate reactions caused by rice husk ash on the system; the hydration process and hydration products of steel slag powder can reduce the alkalinity in the system, while sulfate activators can not only promote the hydration of steel slag powder, but the sulfate ions in it can also exchange with the alkali ions in the system to further reduce the content of free alkali.

[0028] 4) The cementitious material in the system of this invention is composed of all solid waste raw materials. Compared with conventional concrete, the carbon emissions of concrete prepared by this system can be reduced by more than 80%, the unit cost of concrete can be reduced by 30%, and the construction performance and mechanical properties meet the requirements, which has obvious economic benefits and environmental protection value. Detailed Implementation

[0029] The present invention will be further described below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0030] In the following examples, the rice husk ash used was taken from a biomass power plant in Huanggang City, Hubei Province; the SiO2 content was 88%, the 28-day activity index was 91%, and the median particle size D50 was 4.9 μm.

[0031] The dust collection stone powder used was from Huaxin Cement Co., Ltd., with a fineness of 11.6%, a 28-day activity index of 73%, and a water requirement ratio of 101%.

[0032] The steel slag powder used has a median particle size (D50) of 4.2 μm, a 28-day activity index of 74%, and a specific surface area of ​​475 m². 2 / kg.

[0033] The polycarboxylate superplasticizer used is manufactured by China Construction Western Construction New Materials Technology Co., Ltd., model ZJC-01, with a water reduction rate of 23% and a solid content of 9.8%.

[0034] The sand used was quartz sand with a fineness modulus of 2.6, classified as medium sand in zone two; the stone had a continuous gradation of 5–25 mm and a needle-like / flaky content of 5.8%.

[0035] Example 1

[0036] A green, low-carbon concrete, the preparation method of which includes the following steps:

[0037] 1) Weighing of raw materials: each raw material and its weight percentage are as follows: 120 parts rice husk ash, 160 parts dust collection stone powder, 120 parts steel slag powder, 820 parts sand, 1000 parts stone, 6 parts sodium sulfate, 8 parts polycarboxylate superplasticizer, and 175 parts water.

[0038] 2) Mix rice husk ash, steel slag powder, and dust collection stone powder according to the weighed proportions, and then place them in a high-efficiency ball mill for mechanical grinding for 4 hours. The ball mill speed is set to 600 r / min, steel balls are used as the ball material, and the ball-to-material ratio is 10:1. Stabilize the ground mixture in an oven at 110℃ for 2 hours, and then cool it to room temperature for later use to obtain a low-carbon composite cementitious material.

[0039] 3) First, mix 70% of the total water with the water-reducing agent to obtain a water-reducing agent solution. Add the water-reducing agent solution into the mixer, and then immediately add the low-carbon composite cementitious material. Start the mixer and add sodium sulfate evenly while stirring. This process lasts for 2 minutes.

[0040] 4) After 2 minutes, add sand to the mixer that is mixing, then add gravel, and mix again for 3 minutes. Add the remaining water during the process to obtain the low-carbon early-strength concrete mixture.

[0041] Example 2

[0042] A green low-carbon concrete is prepared in a manner similar to that of Example 1, except that the raw materials and their weight percentages are as follows: 100 parts rice husk ash, 170 parts dust-collecting stone powder, 130 parts steel slag powder, 820 parts sand, 1000 parts stone, 6 parts sodium sulfate, 8 parts polycarboxylate superplasticizer, and 178 parts water.

[0043] Example 3

[0044] A green low-carbon concrete is prepared in a manner similar to that of Example 1, except that the raw materials and their weight proportions are as follows: 130 parts rice husk ash, 160 parts dust-collecting stone powder, 110 parts steel slag powder, 820 parts sand, 1000 parts stone, 6 parts sodium sulfate, 8 parts polycarboxylate superplasticizer, and 175 parts water.

[0045] Comparative Example 1

[0046] A green low-carbon concrete is prepared in a manner similar to that of Example 1, except that the raw materials and their weight proportions are as follows: 120 parts rice husk ash, 160 parts dust-collecting stone powder, 120 parts steel slag powder, 820 parts sand, 1000 parts stone, 0 parts sodium sulfate, 8 parts polycarboxylate superplasticizer, and 180 parts water.

[0047] Comparative Example 2

[0048] A green low-carbon concrete is prepared in a manner similar to that of Example 1, except that the raw materials and their weight percentages are as follows: 220 parts rice husk ash, 180 parts dust-collecting stone powder, 0 parts steel slag powder, 820 parts sand, 1000 parts stone, 6 parts sodium sulfate, 8 parts polycarboxylate superplasticizer, and 175 parts water.

[0049] Comparative Example 3

[0050] A green low-carbon concrete is prepared in a manner similar to that of Example 1, except that the efficient grinding and heating stabilization treatment described in step 2) is not performed.

[0051] Comparative Example 4

[0052] A green, low-carbon concrete is prepared in a manner similar to that of Example 1, except that it is not placed in an oven for stabilization after high-efficiency grinding.

[0053] Comparative Example 5

[0054] A green low-carbon concrete is prepared in a manner similar to that of Example 1, except that in step 2), rice husk ash, steel slag powder, and dust collection stone powder are mixed according to the weighed proportions and stabilized in an oven at 110°C for 2 hours, and then mechanically ground in a high-efficiency ball mill for 4 hours.

[0055] The concrete obtained in Examples 1-3 and Comparative Examples 1-5 were subjected to workability and mechanical property tests, specifically including: measuring the initial flowability and spread of the fresh concrete; molding the prepared concrete into 150mm×150mm×150mm molds for testing the compressive strength of the concrete; and conducting compressive strength tests after curing under standard curing conditions for 3 days and 28 days. The specific test data indicators are shown in Table 1 below.

[0056] Table 1. Performance test results of concrete obtained in the examples and comparative examples.

[0057]

[0058]

[0059] This invention is not limited to the embodiments described above. Those skilled in the art can make various improvements and modifications without departing from the principles of this invention, and these improvements and modifications are also considered within the scope of protection of this invention. Contents not described in detail in this specification are prior art known to those skilled in the art.

Claims

1. A green, low-carbon concrete, characterized in that, The raw materials and their respective weight percentages include: 100-140 parts rice husk ash, 140-180 parts dust-collecting stone powder, 100-140 parts steel slag powder, 780-880 parts sand, 950-1100 parts stone, 4-10 parts activator, 6-10 parts water-reducing agent, and 170-180 parts water; among which, rice husk ash, dust-collecting stone powder, and steel slag powder are first ground and heated to stabilize them to form a low-carbon composite cementitious material. The heating stabilization treatment is performed at a temperature of 110~150℃ for 2~6 hours. The activator is a sulfate activator; The rice husk ash contains SiO2 content >85%, activity index >90%, and median particle size D50 <6µm; The dust-collecting stone powder has a sieve residue fineness of 9-13% on a 45µm square hole sieve, a 28-day activity index greater than 70%, and a water requirement ratio of 95-105%. The steel slag powder has a median particle size D50 of less than 5 μm, a 28-day activity index greater than 70%, and a specific surface area greater than 450 m². 2 / kg; The grinding step uses a rotation speed > 500 r / min, a grinding time of 3~5 h, and a ball-to-material ratio of 10~15:

1.

2. The green low-carbon concrete according to claim 1, characterized in that, The fineness modulus of the sand is 2.5~2.8, which is medium sand in Zone II; the stone has a continuous gradation of 5~25mm, and the content of needle-like and flaky particles is less than 6%.

3. The green low-carbon concrete according to claim 1, characterized in that, The water-reducing agent has a water reduction rate of 15-25%.

4. The method for preparing green low-carbon concrete according to any one of claims 1 to 3, characterized in that, Includes the following steps: 1) Weighing of raw materials: each raw material and its weight percentage include: 100-140 parts rice husk ash, 140-180 parts dust collection stone powder, 100-140 parts steel slag powder, 780-880 parts sand, 950-1100 parts stone, 4-10 parts activator, 6-10 parts water reducing agent, and 170-180 parts water. 2) Mix the weighed rice husk ash, steel slag powder, and dust collection stone powder, then grind them, then heat and stabilize them, and cool them to obtain a low-carbon composite cementitious material. 3) First, mix some water with the water-reducing agent evenly to obtain a water-reducing agent solution. Add the water-reducing agent solution into the mixer, add the low-carbon composite cementitious material, and then add the activator under stirring conditions. 4) Continue to add sand and stone in sequence under stirring conditions, stir and process, and add the remaining water during this process to obtain green low-carbon concrete.

Citation Information

Patent Citations

  • Preparation method of concrete mixed with dust collection stone powder and mineral powder based on strength and chloride ion permeation resistance double indexes

    CN115745501A

  • Alkali-activated steel solid waste-based low-carbon concrete material and preparation method thereof

    CN118271064A